Answer:(a+b)^2+(ab+a+b)2
Step-by-step explanation:
You break it up into two part, based on the exponents.
(a^2+b^2)+(2ab+2a+2b)
Now you can factor out from each...
(a+b)^2+(ab+a+b)2
Answer: (x+y+2)(x+y)
Step-by-step explanation:
Using square roots and factorising
using the rate of Rs. 124.40 per using US dollar, find the US dollar for Rs. 158610.
Answer:
1275 USD
Step-by-step explanation:
124.40 Rs -----> 1 USD
158610 Rs -----> x USD
124.40x=158610
×=158610/124.40
x=1275 USD
Jacob is calculating the amount of time it takes a rocket to get to the moom
Answer:
16 hours
Step-by-step explanation:
Speed=distance/time
Let S be speed, D be distance, and t be time.
Let's solve the speed equation for t since we are looking for time, t.
[tex]S=\frac{D}{t}[/tex]
Multiply both sides by t:
[tex]St=D[/tex]
Divide both sides by S:
[tex]t=\frac{D}{S}[/tex]
So our distance is 239000 and our speed is 250 so plug them in:
[tex]t=\frac{239000}{250}[/tex]
Putting into the calculator now:
t=956 minutes (I knew this was in minutes because the speed was 250 miles per minute)
We need to convert this to hours. 60 minutes=1 hour.
60 minutes=1 hour
956 minutes=x hours
You can setup a proportion if you don't know you just need to take 956 and divide it by 60. Like so:
[tex]\frac{60}{956}=\frac{1}{x}[/tex]
Cross multiply:
[tex]60x=956(1)[/tex]
[tex]60x=956[/tex]
Divide both sides by 60:
[tex]x=\frac{956}{60}[/tex]
Putting into calculator now:
x=15.9333333333333 which mean we have almost 16 hours
What are the solutions to the equation 3(x-4)^2=27
Answer:
x=1, x=7
Step-by-step explanation:
Firstly, you can simplify by dividing both sides by 3, which will make the equation easier to simplify:
(x-4)^2=9
Next, you can take the square root of each side, which will cancel the square, and make the 9 even easier to work with:
(x-4)=(± )3
*Note the (± ) sign, this is because there is a positive and negative answer*
After this, you will basically have two equations:
(x-4)=3
and
(x-4)=-3
You are going to solve both to get both answers, but lets start with the positive first:
x-4=3 Add 4 to both sides to get an x= equation
x=7
And it's the same thing for the negative:
x-4=-3 Add 4 to both sides to get an x= equation
x=1
Hope this helps
Final answer:
To solve the equation 3(x-4)²=27, divide by 3 to get (x-4)²=9, then take the square root to find the solutions x=7 and x=1.
Explanation:
When we're tasked with solving a quadratic equation, such as 3(x-4)²=27, we first need to get it into the standard form of a quadratic equation, which is ax² + bx + c = 0. To do so in this case, we can divide both sides of the equation by 3 to isolate the squared term, yielding (x-4)²= 9. We then take the square root of both sides, giving us x - 4 =3. Solving for x results in two solutions: x = 4 + 3 and x = 4 - 3, which simplifies to x = 7 and x = 1 respectively. These are the solutions to the given equation.
To verify these solutions, you can substitute them back into the original equation to ensure that they satisfy the equation, which in this case, they will. This critical step confirms the accuracy of our solutions.
Two lines and a transversal form corresponding angles that are congruent. Describe the two lines
Answer:
parallel
Step-by-step explanation:
If you have two lines and a transversal that form corresponding angles that are congruent. Then the alternate interior angles are congruent and the same-side interior (some people call these consecutive angles) are supplementary.
This has to deal with Parallel Lines Theorem or the Converse of Parallel Lines Theorem.
The lines would be parallel.
Two lines will be parallel.
What is corresponding angle?When two lines are cut by a transversal then the angles formed relatively same position in their respective line at the intersection transversal and two lines are called corresponding angles.
What is converse of corresponding angles theorem?
Converse of corresponding angles theorem states that When two lines are cut by a transversal and the formed corresponding angles are congruent then the two lines will be parallel.
Here given that two lines and transversal are forming corresponding angles which are congruent. So by converse of corresponding angles theorem, the two lines will be parallel to each other.
Therefore two lines will be parallel.
Learn more about corresponding angle
here: https://brainly.com/question/2496440
#SPJ2
Peter and Angad win some money and share it in the ratio 6:1. Peter gets £30 more than Angad. How much did they get altogether?
Final answer:
The total amount of money Peter and Angad won and shared in the ratio 6:1, with Peter getting £30 more than Angad, is £72.
Explanation:
Peter and Angad win some money and share it in the ratio of 6:1. If Peter gets £30 more than Angad, to find out how much they got altogether, we can use this ratio to express their winnings in terms of algebra. Let the amount Angad gets be x. Then Peter gets x+£30 since he gets £30 more than Angad. According to the ratio 6:1, Peter's share would be 6 times Angad's share; this gives us the equation 6x = x+ £30.
To solve for x, combine like terms: 6x - x = £30, which simplifies to 5x = £30. Divide both sides by 5 to find x: x = £6. Now that we know Angad receives £6, we can find Peter's share by multiplying Angad's share by 6: 6*£6 = £36. Add the £30 difference to get Peter's total: £36+£30 = £66.
To find the total amount they got altogether, add Angad's share and Peter's share together: £66 + £6 = £72.
Subtract. 5x^2-5x+1-(2x^2+9x-6)
The answer is:
[tex]3x^{2} -14x+7[/tex]
Why?To solve the problem we need to add/subtract like terms. We need to remember that like terms are the terms that share the same variable and the same exponent.
For example, we have:
[tex]x^{2} +2x+3x=x^{2} +(2x+3x)=x^{2}+5x[/tex]
We have that we were able to add just the terms that were sharing the same variable and exponenr (x for this case).
So, we are given the expression:
[tex]5x^2-5x+1-(2x^2+9x-6)=5x^{2}-2x^{2}-5x-9x+1-(-6)\\\\(5x^{2}-2x^{2})+(-5x-9x)+(1-(-6))=3x^{2}-14x+7[/tex]
Hence, the answer is:
[tex]3x^{2} -14x+7[/tex]
Have a nice day!
HELP!!!! PLEASE need help now its an emergency.
Answer:
121,6
Step-by-step explanation:
Since the only difference between the triangles are the letters and a few missing numbers, just replace the letters to get your answer. A and D are the same B and E are the same and C and F are the same. So the measurement of angle A is 121 degrees and the length of AB is 6
Given the function f(x)=-5x^2-x+20 find f(3)
Answer:
-28
Step-by-step explanation:
-5(3)^2 - 3 + 20
-5*9 - 3 + 20
-45 -3+ 20
-48+ 20
-28
Hope it helps!
Find the value 7+3^2(-5+1)divided by 2
The expression 7 + 3^2(-5 + 1) divided by 2 equals -14.5, after calculating the exponent, solving the parenthesis, multiplying, adding to 7, and then dividing by 2.
Explanation:To find the value of the expression 7 + 32(-5 + 1) divided by 2, follow these steps:
Calculate the exponent: 32 = 9.Solve the parenthesis: (-5 + 1) = -4.Multiply the results from steps 1 and 2: 9 * -4 = -36.Add the result from step 3 to 7: 7 - 36 = -29.Finally, divide by 2: -29 / 2 = -14.5.The value of the expression is -14.5.
Learn more about Solving Expressions here:https://brainly.com/question/36578689
#SPJ2
You have a total of $1760 to invest. Account A pays 7% annual interest and account B pays 4% annual interest. How much should you invest in each account if you would like the investment to earn $ 95 at the end of one year? Let A represent the amount of money invested in the account that earns 7% annual interest and let B represent the amount of money invested in the account that earns 4% annual interest. Complete the system of linear equations to solve the problem.
Answer:
You should invest $820 in account A and $940 in account B
Step-by-step explanation:
* Lets use the system of linear equations to solve the problem
- Simple Interest Equation I = Prt , Where:
# P = Invested Amount
# I = Interest Amount
# r = Rate of Interest per year in decimal; r = R/100
# t = Time Period involved in months or years
* Lets solve the problem
- The total money invested is $1760
- Account A pays 7% annual interest
- Account B pays 4% annual interest
- Let A represent the amount of money invested in the account A
- Let B represent the amount of money invested in the account B
- You would like to earn $ 95 at the end of one year
∴ The interest from both accounts at the end of one year is $95
- Lets write the equations
# Account A :
∵ Account A has $A invested
∴ P = $A
∵ Account A pays 7% annual interest
∴ r = 7/100 = 0.07
∵ t = 1 year
∵ I = Prt
∴ I = A(0.07)(1) = 0.07A
# Account B :
∵ Account B has $B invested
∴ P = $B
∵ Account A pays 4% annual interest
∴ r = 4/100 = 0.04
∵ t = 1 year
∵ I = Prt
∴ I = B(0.04)(1) = 0.04B
- The total amount of interest from both accounts at the end of one
year is $95
∴ I from A + I from B = 95
∴ 0.07A + 0.04B = 95 ⇒ multiply both sides by 100
∴ 7A + 4B = 9500 ⇒ (1)
- The total money to invest in both accounts is $1760
∵ Account A has $A invested
∵ Account B has $B invested
∴ A + B = 1760 ⇒ (2)
* Lets solve the system of equations to find the amount of money
invested in each account
- Multiply equation (2) by -4 to eliminate B
∵ A + B = 1760 ⇒ × -4
∴ -4A - 4B = -7040 ⇒ (3)
- Add equation (1) and (3)
∵ 7A + 4B = 9500 ⇒ (1)
∵ -4A - 4B = -7040 ⇒ (3)
∴ 7A - 4A = 9500 - 7040
∴ 3A = 2460 ⇒ divide both side by 3
∴ A = 820
- Substitute the value of A in equation (1) or (2)
∵ A + B = 1760 ⇒ (2)
∴ 820 + B = 1760 ⇒ subtract 820 from both sides
∴ B = 940
- From all above
* You should invest $820 in account A and $940 in account B
Which equation can be solved by using this expression?
Answer:
The correct answer option is B. 2 = 3x + 10x^2
Step-by-step explanation:
We are to determine whether which of the given equations in the answer options can be solved using the following expression:
[tex]x=\frac{-3 \pm\sqrt{(3)^2+4(10)(2)} }{2(10)}[/tex]
Here, [tex]a = 10, b = 3[/tex] and [tex]c=-2[/tex].
These requirements are fulfilled by the equation 4 which is:
[tex]12=3x+10x^2[/tex]
Rearranging it to get:
[tex]10x^2+3x-2=0[/tex]
Substituting these values of [tex]a,b,c[/tex] in the quadratic formula:
[tex]x= \frac{-b \pm \sqrt{b^2-4ac} }{2a}[/tex]
[tex]x= \frac{-3 \pm\sqrt{(3)^2-4(10)(-2)} }{y}[/tex]
The apother is 4 m and a side is 5.8 m. What is the area
of the pentagon? Round to the nearest whole number.
Answer:
58 m^2.
Step-by-step explanation:
The area of one of the 5 triangles is:
1/2 * 5.8 * 4 = 11.6 m^2
So the area of the pentagon
= 5 + 11.6
= 58 m^2
Answer:
The area is 58 meters squared.
Step-by-step explanation:
Since the pentagon is conveniently split into 5 separate but equal triangles, we only need to find the area of 1 triangle to find the rest. The area of triangles, as I'm sure you know, is 1/2bh. Using this equation, we get (1/2)x4x5.8. This equals 11.6. This is the area of one of the triangles. There are 5 triangles, so we multiply the area of 1 triangle by 5. 11.6x5= 58 meters squared. Hope this helped. :)
A = B/2 = C/5 a:b:c=?
Answer:
[tex]\large\boxed{A:B:C=\dfrac{1}{10A}}[/tex]
Step-by-step explanation:
[tex]A=\dfrac{B}{2}=\dfrac{C}{5}\\\\A=\dfrac{B}{2}\qquad\text{multiply both sides by 2}\\\\2A=B\to\boxed{B=2A}\\\\A=\dfrac{C}{5}\qquad\text{multiply both sides by 5}\\\\5A=C\to C=5A\\\\A:B:C=A:2A:5A=1:2:5A=\dfrac{1}{2}:5A=\dfrac{1}{2}\cdot\dfrac{1}{5A}=\dfrac{1}{10A}[/tex]
Which statement is NOT true about the slope of a straight-line graph?
A) Slope is a measure of the steepness of the line
B) Slope is the ratio of vertical change to horizontal change
C) Slope is zero if the line is horizontal
D) Slope is 1 if the line is vertical
Answer:
Option D. Slope is 1 if the line is vertical
Step-by-step explanation:
we have
Part A) Slope is a measure of the steepness of the line
The statement is true
Because, the steepness of a line is measured by the absolute value of the slope.
Part B) Slope is the ratio of vertical change to horizontal change
The statement is true
Because the formula to calculate the slope between two points is equal to
[tex]m=\frac{y2-y1}{x2-x1}[/tex]
so
Is the ratio of vertical change to horizontal change
Part C) Slope is zero if the line is horizontal
The statement is true
Because If the line is horizontal, the y-coordinate of two points is the same
therefore
The vertical change is equal to zero
Part D) Slope is 1 if the line is vertical
The statement is Not true
Because, if the line is vertical the slope is undefined
Answer:
Slope is 1
1
if the line is vertical.
Step-by-step explanation:
Rip van Winkle fell asleep for a very long time. When he fell asleep, his beard was 8 millimeters long, and each passing week it grew 2 additional millimeters.
Graph the length of Rip van Winkle's beard (in millimeters) as a function of time (in weeks).
Please help me to understand how to graph this problem.
A function that models the situation is f(x) = 2x + 8.
A graph of the length of Rip van Winkle's beard (in millimeters) as a function of time (in weeks) is shown in the picture below.
In Mathematics, the slope-intercept form of the equation of a straight line refers to the general equation of a linear function and it is represented by this mathematical equation;
y = mx + b
where:
m represents the slope.x and y are the points.b represents the y-intercept or initial value.Since Rip van Winkle's beard was 8 millimeters long when he fell asleep, and each passing week it grew 2 additional millimeters, we can logically deduce the following parameters;
slope, m = 2.
initial value or y-intercept, b = 8.
In this context, an equation for the function that relates the length of his beard (in millimeters) to time (in weeks) can be written as follows;
y = mx + b
f(x) = 2x + 8
May someone plz help me
Answer:
y = -1/2 x +5
10 weeks
Step-by-step explanation:
The y intercept is 5 ( That is is the point where x=0)
Our slope is rise over run or 1 lb /2 weeks
We know this is negative because the cat is losing the weight
slope = -1/2
The equation in slope intercept form is
y= mx + b where m is the slope and b is the y intercept
y = -1/2 x +5
We need to determine when y=0 to find when the cat loses all 5 lbs
0 = -1/2 x +5
Subtract 5 from each side
0-5 = -1/2x +5-5
-5 = -1/2x
Multiply each side by -2 to get x alone
-5 *-2 = -1/2x * -2
10 = x
It will take 10 weeks
Answer:
y = -1/2x + 5
It will take 10 weeks for the cat to lose 5 pounds.
Step-by-step explanation:
Find slope
Take 2 points (2,4) (6,2)
y2 - y1/x2 - x12 - 4/6 - 2slope = -1/2
y-intercept
(0,5)
y = mx + b form
m represents slope
b represents y-intercept
y = -1/2x + 5
Find the number of weeks it will the cat to lose 5 pounds
Set y = to 0, to find when the cat loses weight
0 = -1/2x + 5
Subtract 5 in both sides
-5 = -1/2x
Isolate the variable by getting rid of the denominator
-1/2x * 2 = -x
2 * - 5 = -10
Simplify
-x = -10
Divide both sides by -1
-x/-1 = x
-10/-1 = 10
Simplify
x = 10
Answer
It will take 10 weeks for the cat to lose 5 pounds
what is the solution to x=√3x+10?
Answer:
x=5
Step-by-step explanation:
Given
[tex]x=\sqrt{3x+10}[/tex]
Squaring on both sides
[tex]x^2=(\sqrt{3x+10})^2 \\x^2=3x+10\\x^2-3x-10 = 0\\x^2-5x+2x-10 = 0\\x(x-5)+2(x-5) = 0\\(x-5)(x+2)=0\\x=5\\and\\x=-2[/tex]
Since putting -2 gives us:
[tex]-2=\sqrt{3(-2)+10} \\-2=\sqrt{-6+10}\\-2=\sqrt{4}\\-2\neq 2[/tex]
2 is an extraneous solution.
Therefore, the solution to x=√3x+10 is x=5 ..
What is 80% of 80 round to the nearest hundreds
Answer:64
Step-by-step explanation:
Rodney is given two linear equations: x – y = 11 and 2x + y = 19. What value of x should he get as a solution for this system of linear equations
Answer:
x = 10
Step-by-step explanation:
Given the 2 equations
x - y = 11 → (1)
2x + y = 19 → (2)
Adding the 2 equations term by term eliminates the term in y, that is
(x + 2x) + (- y + y) = (11 + 19), simplifying gives
3x = 30 ( divide both sides by 3 )
x = 10
Answer:
x = 10
Step-by-step explanation:
We know that Rodney is given the following two linear equations and we are to find the value of x at which he would get a solution for this system of linear equations:
[tex] x - y = 1 1 [/tex] - (1)
[tex] 2 x + y = 1 9 [/tex] - (2)
From (1):
[tex]x=11+y[/tex]
Substituting this value of x in (2):
[tex]2(11+y)+y=19[/tex]
[tex]22+2y+y=19[/tex]
[tex]3y=19-22[/tex]
[tex]y=-\frac{3}{3}[/tex]
[tex]y=-1[/tex]
Substituting this value of y in (1) to find x:
[tex]x=11+(-1)[/tex]
x = 10
The Outlanders Club keeps track of the mean and median ages of its members. The ages of the six members are 26, 18, 42, 22, 38,
and 34. Which will increase more, the mean or the median, when a new member who is 65 years old joins?
What is the y-intercept of the function,represented by the table of values below?
Answer:
8
Step-by-step explanation:
So the y-intercept is not given by your table because there is no x that is listed as 0.
But don't fret; we can still find it.
Let's see if the function is linear by seeing if we have the same slope per two points in the table.
For the first pair ( the points (-2,16) and (1,4) ), x increased by 3 and the y decreased by 12 so the slope there is -12/3=-4.
Now looking at the next pair ( the points (1,4) and (2,0) ), x increased by 1 while y decreased by 4 so the slope is -4/1=-4.
So the function appears to be linear.
So the slope-intercept form of a line is y=mx+b where m is slope and b is y-intercept.
We already found the slope from earlier which is m=-4.
So the equation so far is y=-4x+b.
Now to find b, the y-intercept, we need to use a point (x,y) on the line along with y=-4x+b.
Let's see my favorite on the list of points is (2,0).
y=-4x+b with (x,y)=(2,0)
0=-4(2)+b
0=-8+b
8=b
So the y-intercept is 8.
Which polynomial represents the sum below (4x^2+1)+(4x^2+x+2)
Answer:
8x^2 + x + 3.
Step-by-step explanation:
(4x^2+1)+(4x^2+x+2)
= 8x^2 + x + 2 + 1
= 8x^2 + x + 3.
Answer:
The polynomial [tex]8x^2+x+3[/tex] represents the sum of given expression.
Step-by-step explanation:
The given expression is
[tex](4x^2+1)+(4x^2+x+2)[/tex]
We need to find the sum of given polynomials.
Open the brackets.
[tex]4x^2+1+4x^2+x+2[/tex]
Combine like terms.
[tex](4x^2+4x^2)+x+(1+2)[/tex]
On further simplification we get
[tex]8x^2+x+3[/tex]
Therefore the polynomial [tex]8x^2+x+3[/tex] represents the sum of given expression.
Nat bought 3 colas for $1.25 each, 2 hot-dogs for $2.50 each, and a hamburger for $6.50. He paid with $20 bill. How much money does Nat have left?
Answer:
$4.75 is how much money is left over
Step-by-step explanation:
3* 1.25= 3.75
2* 2.50= 5.00
1* 6.50+ 6.50
5.00+3.75+6.50= 15.25
20- 15.25= 4.75
Final answer:
Nat spent a total of $15.25 on colas, hot dogs, and a hamburger. After paying with a $20 bill, he has $4.75 left.
Explanation:
To calculate how much money Nat has left after his purchases, we will add up the cost of the items he bought and subtract that total from the $20 bill he used for payment.
Cost of 3 colas: 3 × $1.25 each = $3.75
Cost of 2 hot-dogs: 2 × $2.50 each = $5.00
Cost of 1 hamburger: $6.50
Now we'll sum these amounts to find the total spending:
Total spending = $3.75 + $5.00 + $6.50 = $15.25
Next, we subtract the total spending from the $20 bill:
Change = $20.00 - $15.25 = $4.75
Therefore, Nat has $4.75 left after his purchase.
m2 - 36 = 0
Several solutions please
Answer:
m = ±6
Step-by-step explanation:
m^2 -36 =0
Add 36 to each side
m^2-36 +36 = 0+36
m^2 = 36
Take the square root of each side
sqrt(m^2) = ±sqrt(36)
m = ±6
Answer:+6 or -6
Step-by-step explanation:m^2 - 6^2
it becomes difference of two squares,
(m+6) (m-6)=0
m-6=0,m=6
m+6=0,m=-6
Which pair of points will determine a line
parallel to the x-axis?
(1) (2,3), (2,-5)
(2) (5, 4), (-1, 4)
(3) (2, 2), (-1, -1)
(4) (3, 4), (6,2)
Please help I don’t get it I’m stuck:(
Answer:
2) (5,4) and (-1,4)
These have the same y so this line will be horizontal making it parallel to the x-axis.
Step-by-step explanation:
All horizontal lines are parallel to each other. The x-axis is horizontal. So we are looking for a horizontal line. On a horizontal line, all the y-coordinates are the same; their equation is in the form y=a number after all.
Anyways we looking for a pair of points with the same y-coordinate.
1) (2,3) and (2,-5)
These have the same x-coordinate so this line is vertical. This would actually be perpendicular to the line given.
2) (5,4) and (-1,4)
These have the same y so this line will be horizontal making it parallel to the x-axis.
3) (2,2) and (-1,-1)
y's aren't the same so not horizontal
x's aren't the same so not vertical
4) (3,4) and (6,2)
y's aren't the same so not horizontal
x's aren't the same so not vertical
For a pair of points to be parallel to the x-axis, the points have to consist the same x-coordinates.
In this case, only (1) (2,3), (2,-5) have the same x-coordinates.
Therefore, the answer is (1) (2,3), (2,-5).
Hope it helps!
The length of a rectangle is three times its width, and its area is 9 cm2
. Find the
dimensions of the rectangle.
Answer:
3√3 cm. = l
√3 cm. = w
Step-by-step explanation:
l = 3w
9 = 3w[w] ↷
9 = 3w² [Divide by 3]
3 = w² [Take the square root]
√3 = w [plug this back into the top equation to get a length of 3√3 cm.]
I am joyous to assist you anytime.
What is the volume of the composite figure?
12in
4 in
3 in.
7 in.
Answer:
Step-by-step explanation:
[tex]V_p = b \cdot h \cdot w[/tex], where b, h, w are base, height and width respectively.
[tex]V_{sp} = \frac{1}{3} \cdot {A_b} \cdot h[/tex], where h is the height, and A_b is the area of the base.
First let's calculate the volume of the paralelipiped by the first formula.
[tex]V_p = 7 \cdot 4 \cdot 3 = 84 in^2[/tex]
Then let's find out the height of the pyramid, which is 12 - 4 = 8 in.(See drawing)
Then the area of the base of the square pyramid is simply.
[tex]A_r = 3 \cdot 7 = 21 in^2[/tex]
Now we can find the volume of the pyramid.
[tex]V_{sp} = \frac{1}{3} \cdot 21 \cdot 8 = 56 in^3[/tex]
To find the total volume, let's add both volumes.
[tex]V_T = 84 + 56 = 140 in^3[/tex]
The volume of the composite figure is calculated by adding the volume of the individual shapes that make up the figure. For a figure composed of a rectangular prism and a triangular prism, you would calculate both volumes separately and add them together, giving a total volume of 186 in³ based on the dimensions provided.
Explanation:In mathematics, the term volume refers to the amount of space occupied by a 3-dimensional object.
The composite figure you've given seems to include a rectangular prism and an extruded triangle (or possibly a rectangular prism attached to a triangular prism, without information about the orientation of the shapes, we cannot be certain).
For example, if it were a rectangular prism attached to a triangular prism, we would find the volume of both separately and then add them together. The volume of the rectangular prism would be found by length*width*height (12 in*4 in*3 in=144 in³). The volume of triangular prism would be 1/2*base*height*length (1/2*4 in*3 in*7 in = 42 in³). Adding them together, the volume of the composite figure would be 186 in³.
Learn more about Volume of Composite Figures here:https://brainly.com/question/33058633
#SPJ2
PLZ HELP, WILL GIVE BRAINLIEST
What is the value of x?
A.
73°
B.
45°
C.
35°
D.
25°
Answer:
x = 35
Step-by-step explanation:
The sum of the 3 angles in a triangle = 180°
Subtract the sum of the 2 base angles from 180 for angle at vertex
vertex = 180° - (73 + 51)° = 180° - 124° = 56°
The vertex angle is composed of x and 21, so
x + 21 = 56 ( subtract 21 from both sides )
x = 35
Follow the steps and finish the solution.
7(x-3) = 28
Distributive property
7x-21 = 28
Addition property of equality
7x = 49
Division property of equality
X
=
What is the value of x?
07
O 42
O 56
Mark this and return
Save and Exit
Save and Exit
Next
Next
Submit
Answer:
x=7
Step-by-step explanation:
7(x-3) = 28
Distributive property
7x-21 = 28
Addition property of equality
7x = 49
Division property of equality
7x/7 = 49/7
x = 7
The value of x is 7 ..
Answer:
7
Step-by-step explanation:
Find the tan θ when sin θ= -cos θ and θ is in quadrant IV
Answer:
Step-by-step explanation:
sin θ= - cos θ
if : cos θ ≠ 0
you have : tan θ = -1
tan θ = - tan π/4
tan θ = tan(- π/4 )
θ = - π/4 +kπ k ∈ Z
calculate: k when θ is in quadrant IV : 3π /2 ≤ θ ≤2π
3π /2 ≤ - π/4 +kπ ≤2π
add π/4: 3π /2 + π/4 ≤ - π/4 +kπ+π/4 ≤2π +π/4
7π/4 ≤ kπ ≤9π/4
7/4 ≤ k ≤9/4
1.75 ≤ k ≤ 2.25
k ∈ Z : k =2
so : θ = - π/4 +2π
θ = 7π/4
θ = 7(180°)/4 = 315°